1994
DOI: 10.1007/bf00185441
|View full text |Cite
|
Sign up to set email alerts
|

Blood vessels in epiphyseal cartilage of human fetal femoral bone: a scanning electron microscopic study of corrosion casts

Abstract: Formation of intrachondral vessels (cartilage canals) in the proximal femoral epiphysis was studied in 13- to 22-week-old human fetuses using a corrosion casting technique and scanning electron microscopy. Several successive morphological stages of angiogenesis occurring inside the hyaline cartilage were distinguished. The process of cartilage vascularization starts with the formation of hairpin loops sent off from the perichondrial vascular network into the adjacent cartilage. A capillary glomerulus is then f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 12 publications
7
52
0
Order By: Relevance
“…Cartilage canals have been widely studied in many species (Wilsman & Van Sickle, 1970 ;Haines, 1974 ;Visco et al 1990 ;Ganey et al 1992) and the morphology and ultrastructure of the vessels within them have been also described (Stockwell, 1971 ;Wilsman & Van Sickle, 1972 ;Skawina et al 1994 ;Ganey et al 1995). Cartilage canals seem to be species specific for analogue cartilages as shown in man (Nelson et al 1960 ;Levene, 1964), rabbit (Gothman, 1960 ;Ganey et al 1992) and other species (Levene, 1964).…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…Cartilage canals have been widely studied in many species (Wilsman & Van Sickle, 1970 ;Haines, 1974 ;Visco et al 1990 ;Ganey et al 1992) and the morphology and ultrastructure of the vessels within them have been also described (Stockwell, 1971 ;Wilsman & Van Sickle, 1972 ;Skawina et al 1994 ;Ganey et al 1995). Cartilage canals seem to be species specific for analogue cartilages as shown in man (Nelson et al 1960 ;Levene, 1964), rabbit (Gothman, 1960 ;Ganey et al 1992) and other species (Levene, 1964).…”
Section: mentioning
confidence: 99%
“…Within the cartilage, hypertrophic chondrocytes begin to develop ; a loss of resistance with degeneration of the physis (van den Hooff, 1964 ;Haines, 1974 ;Brown & McFarland 1992) permits fibrovascular penetration starting from metaphyseal vessels rather than neighbouring vascular territories such as the periosteal or capsular regions. In man (Trueta, 1957 ;Skawina et al 1994) and in other animals (Thorp & Dixon, 1991 ;Hayashi, 1992 ;Brown et al 1993) the development of the vasculature and ossification process in the femoral head differs, due to blood vessel penetration into the cartilage in an earlier age when a critical mass of cartilaginous tissue develops (Ganey et al 1992(Ganey et al , 1995. The sources of blood vessels in the femoral head are correlated with the presence of various neighbouring vascular territories, as supplied by the diaphyseal microcirculation in the rat, or also by the teres ligament and Hunter's circle in other larger animals.…”
Section: mentioning
confidence: 99%
“…A view of the bone vascular network injected with resin can also be obtained using a corrosion cast technique (Irino et al 1975;Ohtani et al 1982;Skawina et al 1994); however, most such observations concern marrow and periosteal vessels, while intracortical capillaries were seldom evidenced because of the high viscosity of the resin and difficulty of perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…After perfusion with polymerising resins, it is possible to study the corrosion cast of bone vessel systems using scanning electron microscopy (SEM) (Irino et al 1975;Draenert and Draenert 1980;Ohtani et al 1982;Skawina et al 1994), and to produce three-dimensional representations of the network of vessels that allow stereometric measurements to be made (Minnich et al 1999;Minnich and Lametschwandtner 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These include serial histology in longitudinal or transverse planes, 10) intravenous injection of uorescent dyes, 11) X-ray micro-angiography with infusion of contrast agents, 12,13) and scanning electron microscopy with corrosion casting. 14,15) These techniques, however, still have respective problems related to sensitivity or manipulation dif culties when applied to the analysis of the vascular patterns of mouse bones. 16) Previously, Pazzaglia et al 17) reported a visualization method using black China ink in full-thickness specimens of rabbit femurs.…”
Section: Introductionmentioning
confidence: 99%